Behavioral Finance - An Emerging Theory : A Review Study - Manzoor, Arfat; Jan, Andleebah; Shafi, Mohammad (Indian Journal of Research in Capital Markets, 2023)
Purpose : This paper debated market efficiency and asset pricing through an extensive review of literature in favor as well as against the well-known efficient market hypothesis (EMH). The purpose of this paper is to provide a comprehensive literature review of behavioral finance to label it as an alternate theory of asset pricing. Methodology/Design/Approach : In this paper, the literature review is divided into three parts. Part-1 provides a review of EHM, its dominance, and downfall. Part-2 discusses the rise of behavioral finance as an alternate theory, and part-3 discusses the influencing factors of investment behavior. Three criteria were set for the selection of the articles. First, only relevant and most articles published from 2000 – 2022 were selected, and second, the most important articles published before 2000 were also included. Third, only those articles were selected that were published in the English language. Findings : Comprehensive literature review in this paper helped in solving the market efficiency problems. It shows how the concepts of market efficiency and rationality were challenged by the new field of a discipline known as behavioral finance. Through further discussion on behavioral finance, this paper points out many gaps and also suggests how to bridge them. Originality/Value : This is an extensive study that not only discusses the rationality approach of asset pricing through EMH, but also discusses behavioral finance and its relevance to asset pricing. This study can assist the researchers to focus more on behavioral finance and explore more determining factors of the investment behavior of the investors.